Dwelling and configurating materially - Konstantopoulou, Dimitra (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
The article focuses on the relation between “evolution in materials and constructing systems” and “evolution in architecture”, rephrased as relation between constructing and dwelling. Architectural work is seen as the final phase of a configurative process that comes to be material; at the same time, material assumes the role of vehicle in order for a project to become a tangible fact. Furthermore, both material and scale of an architectural work are thought of as means to approach concrete space and its anthropological connotations. In order to offer an example of this, we enter Aldo van Eyck’s Kindertehuis.